The effects of fifteen evidence-supported therapies for adult depression: A meta-analytic review. (2nd April 2020) - Cuijpers, Pim; Karyotaki, Eirini; de Wit, Leonore; Ebert, David D.
Abstract: Objective: In the past decades, many different types of psychotherapy for adult depression have been developed. Method: In this meta-analysis we examined the effects of 15 different types of psychotherapy using 385 comparisons between a therapy and a control condition: Acceptance and commitment therapy, mindfulness-based cognitive behavior therapy (CBT), guided self-help using a self-help book from David Burns, Beck's CBT, the "Coping with Depression" course, two subtypes of behavioral activation, extended and brief problem-solving therapy, self-examination therapy, brief psychodynamic therapy, non-directive counseling, full and brief interpersonal psychotherapy, and life review therapy. Results: The effect sizes ranged from g = 0.38 for the "Coping with Depression" course to g = 1.10 for life review therapy. There was significant publication bias for most therapies. In 70% of the trials there was at least some risk of bias. After adjusting studies with low risk of bias for publication bias, only two types of therapy remained significant (the "Coping with Depression" course, and self-examination therapy). Conclusions: We conclude that the 15 types of psychotherapy may be effective in the treatment of depression. However, the evidence is not conclusive because of high levels of heterogeneity, publication bias, and the risk of bias in the majority of studies.